PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN PESERTA DIDIK MENGGUNAKAN METODE PREVIEW, QUESTION, READ, SUMMARIZE, TEST (PQRST) DI KELAS IV SD NEGERI 06 PASIR JAMBAK KOTA PADANG: - Citra Sepyusi Ikhsani; Muhammadi (STKIP Subang, 2025)
This study was motivated by the low level of reading comprehension in Indonesian language learning among fourth-grade students at SD Negeri 06 Pasir Jambak in Padang City. The PQRST method was chosen because it can equip students with a systematic structure for reading, understanding, and remembering information effectively. This study was conducted in the fourth grade at SD Negeri 06 Pasir Jambak in Padang City. The subjects of this study were teachers and fourth-grade students, totaling 23 people. This study was a classroom action research (CAR) with a qualitative and quantitative approach, carried out in two cycles, namely cycle I consisting of two meetings and cycle II consisting of one meeting. Each cycle included four stages, namely planning, implementation, observation, and reflection. Data collection techniques included non-tests (observation, interviews, attitude assessment, and skill assessment), tests, and document analysis. The research instruments used were observation sheets, interview sheets, attitude assessment sheets, skill assessment sheets, test sheets, and teaching module assessment sheets. The results of the study show an improvement in terms of teaching modules, teacher activities, student activities, and student learning outcomes. In terms of teaching modules, cycle I obtained an average of 91.66% (A) and cycle II obtained an average of 97.22% (A). In the implementation of teaching aspects in cycle I, the average score was 80.36% (B), while in cycle II, the average score was 92.86% (A). The implementation of learning aspects in cycle I had an average score of 80.36% (B), while in cycle II, the average score was 92.86% (A). The learning outcomes of students in cycle I obtained an average of 76.5 (C) and increased in cycle II with an average of 89.42 (B). Thus, the PQRST method can be said to be an effective learning method in improving students' reading comprehension skills in elementary schools.